Sleep at night and association to aggressive behaviour; Patients in a Psychiatric Intensive Care Unit. (May 2018) - Langsrud, Knut; Kallestad, Håvard; Vaaler, Arne; Almvik, Roger; Palmstierna, Tom; Morken, Gunnar
Abstract: Evaluations of associations between sleep at night and aggressive behaviour in Psychiatric Intensive Care Units (PICU) are lacking. The aims were to explore if sleep duration or night-to-night variations in sleep duration correlated with aggressive behaviour and aggressive incidents the next day and through the whole admission. Fifty consecutive patients admitted to a PICU were included (521 nights) and the nurses registered the time patients were sleeping, aggressive behaviour with The Brøset Violence Checklist (BVC) and aggressive incidents with The Staff Observation Aggression Scale-Revised (SOAS-R). At admission, short sleep duration the first night correlated with aggressive behaviour the next day and admissions with violent incidents had a median of 4.0 h difference in sleep from night one to night two compared to 2.1 h for the rest of the admissions. During the stay, large absolute difference in sleep duration between two nights correlated with aggressive behaviour the next day and short sleep duration was associated with violent incidents. Short sleep duration and night-to-night variations in sleep duration are both associated with increased risk for aggression in PICUs. This observation might help to predict and prevent aggressive incidents. Highlights: Short sleep the first night was associated with aggression the next day. Lack of stability in sleep duration was associated with high BVC score. Patients with schizophrenia seemed more vulnerable to short length of sleep. Other patients seemed more vulnerable to instability in length of sleep.